Peranan Guru Kelas Dalam Pembelajaran Inklusif Pada Anak Berkebutuhan Khusus - Manjari Dewi, Wayan Kesi; Budi Arnawa, I Putu Gede (Metta : Jurnal Ilmu Multidisiplin, 2023)
Educational institutions are not allowed to choose what kind of students will take part in the learning process, basically a teacher has an important role in education, a teacher is required to understand the conditions that all students have, in a learning process of course a teacher will meet with The various characters brought by these students, children with special needs are those who require different educational services adapted to the needs of children in general. So a teacher must have a strategy that is appropriate to the conditions of children with special needs. Inclusive education has a pending role. This educational method is highly recommended for children with special needs. This education provides freedom to all students who have physical disabilities, mental, emotional, and also social. Apart from that, a teacher must also be able to develop the character of tolerance for signs of bullying of children who are different, unlike normal children in general. Realizing a diverse and non-discriminatory education for students. A class teacher has quite a big responsibility because the class teacher is the one who accompanies the child at all times in the learning process rather than other subject teachers. Apart from that, there are many types of conditions that children with special needs have. Of the many types of disorders, a teacher must be able to condition learning methods that are appropriate to the child's condition.